COMPARISON ANALYSIS OF COMPARISON OF SIRTU KALI AND BRISTLE COMBINED AGGREGATE TO PAVEMENT STABILITY ON NGALUPOLO – REKA ROAD (Overview of Lapis Subbase Course - Class B Aggregate) - F. X. Ndale; Veronika M. Radja (Sean Institute, 2023)
The foundation layer of the road serves to carry the burden that works on it and distribute the load to the subgrade. So that the road pavement has adequate bearing capacity and durability, then it needs a comparison of combined crushed stone and Crushed Gravel that meet specifications. The purpose of this study was to determine the comparison of combined crushed stone with crushed gravel. Crushed stone and Crushed Gravel originated from Ende Regency. The Specifications include: Sieve Analysis, Wear, Specific Gravity, Absorption, PI (Plasticity Index) Compaction and CBR (California Bearing Ratio) with SNI Method (Indonesian National Standard). The results of the Class B Combined Aggregate Test, crushed stone were 45.98%, crushed gravel by 52.92% and filler 1.10%, Compaction of 2 kg/cm3 and CBR (California Bearing Ratio) 112%> 60%. Based on these results, the combined grade B gradations meet the 2010 Bina Marga Specifications.